2016
DOI: 10.1128/aac.01044-16
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the New Hepatitis C Virus NS3 Protease Inhibitor Narlaprevir following Single-Dose Use with or without Ritonavir in Patients with Liver Cirrhosis

Abstract: In this study we sought to evaluate narlaprevir (NVR) pharmacokinetics (PK) after a single dose with or without ritonavir (RTV) in cirrhotic versus healthy subjects. NVR at 200 mg was administered to 8 healthy and 8 cirrhotic subjects, and NVR at 100 mg with RTV at 100 mg was administered to 8 healthy and 8 cirrhotic subjects. PK analysis was performed. The geometric mean maximum concentration of a drug in serum (Cmax) and the area under the concentration-time curve from 0 to infinity (AUC0–∞) were 563.1 ng/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Early clinical studies suggested that narlaprevir plus PegIFNa/RBV offered an SVR12 rate up to 59.3% (19/32) in GT1-infected patients (de Bruijne et al, 2010). After a single dose of 200 mg, narlaprevir exposures were higher in cirrhotic patients than in healthy patients (Isakov et al, 2016). A phase 3 trial of narlaprevir (ClinicalTrials, gov identifier: NCT00689390) was terminated due to post-marketing commitments.…”
Section: Ns3/4a Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early clinical studies suggested that narlaprevir plus PegIFNa/RBV offered an SVR12 rate up to 59.3% (19/32) in GT1-infected patients (de Bruijne et al, 2010). After a single dose of 200 mg, narlaprevir exposures were higher in cirrhotic patients than in healthy patients (Isakov et al, 2016). A phase 3 trial of narlaprevir (ClinicalTrials, gov identifier: NCT00689390) was terminated due to post-marketing commitments.…”
Section: Ns3/4a Inhibitorsmentioning
confidence: 99%
“…AV4025 -As an active NS5A inhibitor, AV4025 containing 5- [4-(4-imidazol-4-yl-phenyl)-buta-1,3-diynyl]-1H-imidazole linkers offered potent antiviral activity (EC 50 ¼ 3.4 ± 0.2 pM for GT1b) and favorable pharmacokinetic features in rats and dogs (Ivachtchenko et al, 2014).…”
Section: Ns5a Inhibitorsmentioning
confidence: 99%
“…It demonstrated a good safety profile in addition to being potent in its antiviral activity. In 2016, R‐pharm introduced narlaprevir in the Russian population as the first antiviral drug for the treatment of chronic hepatitis C infection (Figure ) …”
Section: Direct Acting Antiviralsmentioning
confidence: 99%
“…Heterocyclic ring systems bearing a cyclopropane moiety occur in many biologically active natural products, including alkaloids, terpenes, pheromones, herbicides, and fatty acid metabolites . The 3‐azabicyclo[ n .1.0]alkane framework is present in several pharmaceuticals, such as the antibacterial agent trovafloxacin, the anti‐addiction agent amitifadine, the attention deficit hyperactivity disorder (ADHD) drug candidate centanafadine, the analgesic agent bicifadine, the antidepressant drug candidate GSK1360707, and narlaprevir, a protease‐inhibitor drug for the treatment of hepatitis C virus (HCV) infection (Figure ).As a result of their medicinal applications, several synthetic approaches have been reported for the construction of 3‐azabicyclo[ n .1.0]alkane derivatives…”
Section: Figurementioning
confidence: 99%
“…Moreover, 2‐substituted allyl amine derivatives 23 a and 23 b underwent smooth reactions to furnish cyclopropane‐fused bicyclic amidines 24 a and 24 b , respectively, with two contiguous quaternary centers (Table , entry 10). Similarly, 3,3‐disubstituted allyl amine 25 furnished the corresponding 3‐azabicyclo[3.1.0]hexane derivative 26 , a key structural subunit present in narlaprevir (Table , entry 11) . Conspicuously, tosyl azide analogues, such as mesyl azide, benzenesulfonyl azide, and diphenylphosphoryl azide, reacted readily to furnish the corresponding cyclic amidine derivatives 27 a, 27 b , and 27 c , respectively, in good yields (Table , entry 12).…”
Section: Figurementioning
confidence: 99%